The Effectiveness of Sport Life Skills Program for Student-Athletes - Junsu Bae (Cheyuk gwahag yeon-gu, 2022)
PURPOSE The purpose of this study was to apply a life skills program to student-athletes and statistically verify the changes in life skills of the experimental and control group. METHODS Participants were 34 high school Taekwondo athletes (Mage=17.71). They were divided into 18 in the experimental group and 16 in the control group. For eight weeks, the experimental group participated in the life skills program after training and the control group participated in only training as usual. Data were collected by using Life Skills Scale for Student-Athletes (LSSSA), and the participants of two groups filled out the LSSSA before and after the program application. The collected data were analyzed by using repeated measure analysis of variance (ANOVA), and partial η2 (eta squared) was calculated to present the effect size. RESULTS The interaction between time and group was statistically significant in goal setting, coping with stress, positive thinking, and managing emotion among sub-factors of life skills. Partial η2 was interpreted as having a large effect size as it revealed the range of .22 to .51. Therefore, comparing before and after participating in the program, the life skills score of the experimental group among the two groups was significantly improved. CONCLUSIONS Student-athletes who participated in the program experienced positive changes in life skills than those who did not participate in the program.